Religious Fundamentalism - Dr. Kuncheria Pathil CMI (Journal of Dharma, 1990)
Religious pluralism seems to be the irreversible law of the society today. All authentic religions are today accepted as legitimate ways of human salvation or liberation to their believers. Religious tolerance, mutual acceptance of all religions. inter-religious dialogue and cooperation for the common cause of justice. peace and harmony are unmistakably the emerging ethos of our age. But paradoxically our period of history is also marked by the phenomenon of the resurgence of religious fundamentalism which is a temptation to fall back into the exclusivism, absolutism and fanaticism of the bygone age. Christian fundamentalistic sects and movements are mushrooming in the western world and spreading all over under the western economic. cultural and political domination. The Rashtriya Swayam Sevak Sangh (R.S.S.), the Vishwa Hindu Parishad and similar Hindu movements and organizations are addressing today the Hindu masses often in a very fundamentalistic manner and the popular Hindu responses are more along the same line. The Muslim fundamentalistic movements in Iran and other Arab countries also manifest fanaticism and militancy causing fear and suspicion among other believers. The Sikhs in Punjab follow the suit with fundamentalistic movements and' organizations. This is to mention a few conspicuous examples of fundamentalism today.